A Novel Type of Multiterminal Motor Endplate in Human Extraocular Muscles - Liu, Jing-Xia; Domellöf, Fatima Pedrosa (Investigative ophthalmology & visual science, 2018)
To investigate the relation between type of motor endplate, acetylcholine receptor (AChR) subunit composition, and fiber types in human extraocular muscles (EOMs). EOM samples collected from subjects aged 34 to 82 years were serially sectioned and processed for immunohistochemistry, with specific antibodies against different myosin heavy chain (MyHC) isoforms, neurofilament, synaptophysin, and adult epsilon (ε) and fetal gamma (γ) AChR subunits as well as α-bungarotoxin. A novel type of motor endplate consisting of large, multiterminal en plaque endings was found in human EOMs, in addition to the previously well-described single en plaque and multiple en grappe endplates. Such novel endplates were abundant but exclusively observed in myofibers lacking MyHC slow and fast IIa but containing MyHC extraocular (MyHCeom), isoforms. Multiple en grappe endings were found only in myofibers containing MyHC slow-tonic isoform and contained fetal γ AChR subunit. Adult ε and fetal γ AChR subunits, alone or combined, were found in the multiterminal endplates. Distinct AChR subunits were present in adjacent motor endplates of a given myofiber containing MyHCeom. Human EOMs have a more complex innervation pattern than previously described, comprising also a novel type of multiterminal motor endplate present in myofibers containing MyHCeom. The heterogeneity in AChR subunit composition in a given myofiber suggests the possible presence of polyneuronal innervation in human EOMs.